Stepwise dosing protocol for increased throughput in label-free impedance-based GPCR assays - Stolwijk, Judith A.; Mildner, Anne-Kathrin; Kade, Christian; Skiba, Michael; Bernhardt, Guenther; Buschauer, Armin; Hübner, Harald; Gmeiner, Peter; Wegener, Joachim (Journal of Visualized Experiments, 2020)
Label-free impedance-based assays are increasingly used to non-invasively study ligand-induced GPCR activation in cell culture experiments. The approach provides real-time cell monitoring with a device-dependent time resolution down to several tens of milliseconds and it is highly automated. However, when sample numbers get high (e.g., dose-response studies for various different ligands), the cost for the disposable electrode arrays as well as the available time resolution for sequential well-by-well recordings may become limiting. Therefore, we here present a serial agonist addition protocol which has the potential to significantly increase the output of label-free GPCR assays. Using the serial agonist addition protocol, a GPCR agonist is added sequentially in increasing concentrations to a single cell layer while continuously monitoring the sample's impedance (agonist mode). With this serial approach, it is now possible to establish a full dose-response curve for a GPCR agonist from just one single cell layer. The serial agonist addition protocol is applicable to different GPCR coupling types, Gq Gi/0 or Gs and it is compatible with recombinant and endogenous expression levels of the receptor under study. Receptor blocking by GPCR antagonists is assessable as well (antagonist mode).
CRIS-Team Scopus Importer:2020-03-27
Keywords: Agonist; Antagonist; Biochemistry; Cell-based assay; Concentration-response relationship; G-protein coupled receptor (GPCR); Histamine; Impedance; Issue 156; Label-free